Research Progress and Prospect of Reservoir Intelligent Operation - WANG Sen; WANG Xiayu; JIA Wenhao; NI Xiaokuan; LIU Xia (Renmin Zhujiang)
Reservoir operation is an important tool to adapt to climate changes and prevent floods and droughts.With the continuously advancing digitization,a new generation of information technology has begun to integrate with traditional reservoir operations.Based on 445 references collected by CNKI from 2000 to 2023 and 412 references in the core collection database of Web of Science,this paper employs CiteSpace to analyze the status and trend of intelligent operation research.Meanwhile,it systematically sorts out two types of operation technologies including model building and model solving,and six types of information technologies containing knowledge graphs,the internet of things,big data,cloud platform,artificial intelligence,and digital twins.Finally,the intelligent operation provides new ideas for reservoir group operation in river basins,but it still needs further breakthroughs in fields such as thorough perception,data mining,universal model building,and intelligent decision-making.